Optimizing bi-objective redundancy allocation problem with a mixed redundancy strategy - Abouei Ardakan, Mostafa; Zeinal Hamadani, Ali; Alinaghian, Mehdi (ISA transactions, 2015)
Redundancy Allocation Problem (RAP) is a challenging subject which has attracted the attention of many authors. Generally, in the RAP there are two strategies for using the redundant components: active and standby. In this paper a new redundancy strategy, called mixed redundancy, is introduced and considered in a multi-objective optimization RAP. Results demonstrate that the new strategy increases the reliability value of the system considerably. This improvement can be very important for system designers, because the reliability of any systems with the structure of redundant components can be increased by changing the redundancy strategy, not by only adding redundant component. Moreover, this improvement dose not increases the cost and other known physical characteristics of the system. •In this paper the redundancy allocation problem (RAP) for a series-parallel system is considered.•Traditionally there are two main strategies for redundant component namely active and standby.•In this paper a new redundancy strategy which is called “Mixed” redundancy is introduced.•Computational experiments demonstrate that implementing the new strategy lead to interesting results.